(untitled) (Research, Society and Development, 2021)
The present study aims to understand the perception and difficulties faced by teachers of early childhood education about sexuality in the school context. Five educators from a Municipal Center for Early Childhood Education (CMEI) in the Municipality of Foz do Iguaçu - PR participated in the research. As methodological resources, the qualitative approach, the field research, was used, and a semi-structured interview was applied. The data were analyzed in the light of content analysis. From the results, it was understood that teachers of early childhood education face difficulties related to the sexual manifestations of children, since the lack of academic and continuous training of these professionals causes feelings such as insecurity and fear. In addition to presenting a simplistic representation of child sexuality, reducing it to the biological aspect, supporting a complex concept in their own personal beliefs and values. Another difficulty faced by the educators is about the family’s understanding of child sexuality, which becomes a barrier in approaching this theme in the educational context, as there is resistance in the family about the subject. The consolidation of discussions in academic spaces, the implementation of disciplines and interventional techniques in the curriculum of courses; deepening the knowledge of child development; the continuous training of teachers are necessary actions for the construction of practices in the study of child sexuality.